2010
DOI: 10.1523/jneurosci.5488-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Reweighting of Auditory Localization Cues in Response to Chronic Unilateral Earplugging in Humans

Abstract: Localizing a sound source involves the detection and integration of various spatial cues present in the sound waves at each ear. Previous studies indicate that the brain circuits underlying sound localization are calibrated by experience of the cues available to each individual. Plasticity in spatial hearing is most pronounced during development but can also be demonstrated during adulthood under certain circumstances. Investigations into whether adult humans can adjust to reduced input in one ear and learn a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
186
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(215 citation statements)
references
References 49 publications
23
186
6
Order By: Relevance
“…While this work has also suggested that training over a period of days can accelerate accommodation to changes in auditory localization cues, this does not seem to involve a recalibration of the binaural cues (Kumpik et al 2010).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…While this work has also suggested that training over a period of days can accelerate accommodation to changes in auditory localization cues, this does not seem to involve a recalibration of the binaural cues (Kumpik et al 2010).…”
Section: Introductionmentioning
confidence: 66%
“…More recent work using unilateral earplugs to perturb binaural rather than monaural (spectral) cues has demonstrated the capacity for moderate levels of accommodation in mature ferrets (Kacelnik et al 2006) and humans (Kumpik et al 2010). While this work has also suggested that training over a period of days can accelerate accommodation to changes in auditory localization cues, this does not seem to involve a recalibration of the binaural cues (Kumpik et al 2010).…”
Section: Introductionmentioning
confidence: 76%
“…The available data (e.g., Kumpik et al, 2010;Nabelek et al, 1980) indicate that people can quickly re-learn natural localization cues after the cause of the altered cues has been removed, indicating that the natural neural traces in the brain are not significantly altered by learning the new cues.…”
Section: Appendix a Direction Pointingmentioning
confidence: 99%
“…Behavioral studies in adult ferrets showed that unilateral earplugs produced long-term but reversible effects on binaural unmasking (Moore et al, 1999). Follow-up studies investigated the process of relearning to localize sounds after reversible occlusion of one ear, and showed that ferrets and humans improved their localization ability after a training period of only 1 week (Kacelnik et al, 2006;Kumpik et al, 2010).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%